Novel CFD-based full-scale resistance prediction for large medium-speed catamarans. (1st January 2016) - Haase, Max; Zurcher, Konrad; Davidson, Gary; Binns, Jonathan R.; Thomas, Giles; Bose, Neil
Abstract: A novel CFD-based approach is presented that is used in conjunction with model test experiments to predict ship resistance at full-scale Reynolds and Froude numbers. It relies on verification using model scale experiments, including an agreement of integrated shear force with established model-ship correlation lines at model and full-scale, and includes surface roughness effects. One major advantage of the method is that the geometric dimensions of the CFD modelling remain at model scale. CFD simulation results were successfully verified considering the drag of two different catamarans at 1:22 and 1:50 model scale. Furthermore, it is shown that an identical near-wall mesh resolution can be used for both model and full-scale simulations without compromising the accuracy of the shear force component. At full-scale the deviation of resistance between CFD prediction, model test extrapolation and full-scale measurements was less than 5% at Fr = 0.40 and 0.43, showing good agreement. For a novel 130 m catamaran it is shown that variations in full-scale drag for a smooth hull were as low as 5% when comparing extrapolated model scale experiments and CFD predictions. However, at such large Reynolds numbers CFD predictions for correlation and roughness allowance were significantly higher compared to estimates proposed in ITTC guidelines. Abstract : Highlights: A novel CFD-based approach for full-scale drag predictions was developed. Identical computational meshes are used for model and full-scale simulations. Measurements at large medium-speed catamarans were used for validation. Full-scale drag within 5% of results from full-scale measurements of 98 m vessel. Tool usable for numerical model-ship extrapolation or full-scale hull form studies.